Studi Biodegradabilitas Plastik Ramah Lingkungan oleh Larva Tenebrio molitor dan Bioaktivator EM4 - Fika Nur Amaliah; Mochammad Chaerul (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The amount of plastic waste continues to increase with population growth. Decomposition of plastic waste takes tens to hundreds of years. The use of conventional plastics, especially plastic bags that are commonly used by the public, continues to increase, which has a negative impact on the environment. Handling plastic waste using biological methods is an easier, cheaper, and safer solution for the environment. In the degradation process, microorganisms play an important role as decomposers of waste using enzymes in their bodies. However, recent research has revealed that macroorganisms, particularly insects, can accelerate biodegradation. This study examines the biodegradability of environmentally friendly plastics by summarizing scenarios from recent research on plastic biodegradation by macroorganisms and microorganisms. Macroorganisms that have been widely studied for plastic degradation include Tenebrio molitor larvae (T. molitor) and microorganisms derived from EM4 bioactivators. In addition, this study also summarizes the review of the mechanisms, parameters, approaches to biodegradation outcome variables, comparison of the effectiveness of biodegradators using rate biodegradation modeling, and biodegradation reactors, as well as product parameters that are considered so that are considered safe for the environment